THE IMPLEMENTATION OF SAK EMKM IN THE PREPARATION OF FINANCIAL REPORT AT BENGKULU BARBIE SALON MICRO BUSINESS: Implementasi SAK EMKM Dalam Penyusunan Laporan Keuangan Pada Usaha Mikro Barbie Salon Bengkulu - Emi Liana; Neri Susanti; Zahrah Indah Ferina (Realible Accounting Journal, 2022)
This study aims to determine the implementation of financial report preparation based on Financial Accounting Standards for Micro, Small and Medium Entities (SAK EMKM) at Bengkulu Barbie Salon Micro Business which is engaged in beauty care services. The analytical method used in this research is comparative descriptive analysis. The results of the study are based on the presentation of financial reports consisting of daily and monthly financial reports that only show monthly net expenses and income and do not make reports that are in accordance with the Financial Accounting Standards for Micro, Small and Medium Entities (SAK EMKM) which consists of finance position report, income statement and notes to financial statements. This study suggests that the Barbie Salon should make a financial position report, profit and loss statement and notes on financial statements so that the financial statements at the end of each year are listed in accordance with the Financial Accounting Standards for Micro, Small and Medium Entities (SAK EMKM).